Features of the using electronic documentation in the administrative cases of a tourist organization - Kusonskyi , Kostiantyn; Khymytsia, Nataliia (Інформація та соціум, 2021)
Tourism is one of the largest, most profitable and most dynamic sectors of the world economy. Informatization of modern tourist business appears as one of the most characteristic features of the development of this industry in the leading countries of the world tourist market. Modern tourism has entered a stage of its development in which information and its timely transmission plays a decisive role in all areas of tourism, while modern information technologies in tourism are becoming the most important factor in economic growth.